Attic Deme Harbours, the Rural Economy, and State Oversight of Maritime Trade: The Incident at Φωρῶν Λιμήν ([Dem.] 35.28-29) - Lewis, David (Pnyx: Journal of Classical Studies, 2022)
Ancient Greek coastal cities imposed stringent rules on maritime traders arriving from other states, requiring them to sail to the official emporion alone, abide by their laws when in their territory, use local coinage, and pay the relevant taxes. Yet the territories of these cities often contained other limenes (a word that encompasses both artificial harbours and natural moorages) that its legal residents used for fishing and local coastal trade. This article explores the strengths and weaknesses of state oversight of maritime trade by investigating a case study ([Dem.] 35.28-29) where Phaselite merchants allegedly crossed the divide between interstate emporion-trade and intra-state coastal trade, avoiding the emporion at Piraeus and mooring at a local harbour named Phōrōn Limēn (Thieves’ Harbour) yet making use of the market at Piraeus nonetheless. It argues that traditional interpretations of this harbour’s function in terms of smuggling are improbable and that the Phaselites used it instead to conceal important knowledge from their creditors whilst accessing the emporion on foot. This case study also underscores the important economic function of minor relay ports, particularly in terms of the agricultural economy, since these moorages facilitated important transport links between the countryside and city markets.